Nanoformulation: An efficient approach to natural insect repellent formulations - Mehrin Najafzadeh Nansa; Farzaneh Jokarshoorijeh; Nasibeh Tavakoli Hasanaklou; Ramin Hosseni; Massomeh Ghorbanloo; leila Mamani (Journal of Water and Environmental Nanotechnology)
In integrated pest management systems, the usage of repellents has a lot of unrealized potential. Modern insect repellent technologies have greatly benefited from the development of plant essential oils, in particular. As a result, it appears that plant chemicals may one day be used in place of or in addition to chemical insecticides to protect agricultural products. These compounds do not harm the environment and are safer than chemical insecticides. One of the most important plant compounds that is currently getting a lot of attention is plant essential oils. In order to decrease reapplications, toxicity, and cost, research efforts have concentrated on formulations with lower concentrations of active substances and sustained release technologies. Currently, there is a remarkable interest in the development of eco-friendly, secure, and effective pesticides using intelligent, responsive, biodegradable, and biocompatible materials. It was stated that when using nanotechnology to develop and create targeted pesticides with an environmentally sensitive controlled release through chemical modifications and compounds, there is a great potential for developing new formulations.